A p(x)-Kirchhoff Type Problem Involving the p(x)-Laplacian-Like Operators With Dirichlet Boundary Condition - EL OUAARABI, Mohamed; EL HAMMAR, Hasnae; ALLALOU, Chakir; MELLIANI, Said (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
This paper deals with a class of p(x)-Kirchhoff type problems involving the p(x)-Laplacian-like operators, arising from the capillarity phenomena, depending on two real parameters with Dirichlet boundary conditions. Using a topological degree for a class of demicontinuous operators of generalized (S+), we prove the existence of weak solutions of this problem. Our results extend and generalize several corresponding results from the existing literature. Mathematics Subject Classification (2010): 35J60, 35J70, 35D30, 47H11. Received 23 February 2022; Accepted 18 March 2022.